A study on the effect of Salsola tuberculatiformis Botsch. on certain physiological aspects of the ewe, her fetus and neonate - Morgenthal, Johan Casper (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D. Agric.) -- University of Stellenbosch, 1988.